Pond fish culture and socio-economic status of fish farmers in Parbatipur upazila of Dinajpur district, Bangladesh - Kaniz Fatema; Kamrun Naher; Krishna Chandra Roy; Rubaiya Pervin (Journal of Fisheries, 2018)
This study investigates the socio-economic conditions of the fish farmers and aquaculture status in Parbatipur of Dinajpur district during May to October 2016. Majority of the fish farmers belonged to the age group of 31 to 40 years (44.3%) and represented by 68.6% Muslims. Among them 40% had secondary level of education and most of the families were nuclear (64.3%). Farmers were involved in fish culture as their primary (24%) and secondary occupation (53%). Over 80% of the farmers had electricity facilities and 41% of them received health services from the village doctors. Only 9% of the fish farmers received formal training on fish culture. The average aquaculture pond size was 0.18 ha, where 84% ponds were perennial. The average stocking density was 23208 fingerlings ha–1 whereas organic fertilizer, urea and TSP were applied at 8665.4 kg ha–1 yr–1, 210.1 kg ha–1 yr–1 and 133.5 kg ha–1 yr–1 respectively. Pre and post stocking liming doses were 205.7 kg ha–1 yr–1 and 138.4 kg ha–1 yr–1 respectively. Necessary training facilities with institutional supports, credit facilities and extension services could play an important role in improving the fish production.